Perilaku keuangan, dan locus of control, memengaruhi keputusan investasi dengan literasi keuangan sebagai moderasi - Saputri, Evieana R; Erdi, Tio Waskito (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The research conducted aims to test the influence of the variables contained in the study. This research was conducted from February to May 2023.  Data collection was carried out using a questionnaire.  The sample used in this study were students majoring in accounting in Yogyakarta, and the respondents in the study totaled 250 people with purposive sampling technique. The analysis technique used used the Structural Equation Model (SEM) based on Partial Least Squares (PLS). The results showed that financial behavior affects investment decisions, locus of control has a positive effect on investment decisions. Financial literacy is able to strengthen the relationship between financial behavior on investment decisions, and financial literacy is able to strengthen the relationship between locus of control on investment decisions. Based on the results of the analysis of the research that has been tested, it can be concluded that financial behavior, locus of control, and financial literacy affect investment decisions. The existence of financial literacy as moderation can strengthen the relationship between financial behavior variables and locus of control on investment decisions.